The Effect of Independence, Accountability, and Due Professional Care in the Performance of Auditors at the Sumedang Regency Regional Government Inspectorate - Syechbubakar, Sayyidah Fathimah; Hidayat, Gustina; Krisdina, Tiana Fenny (LPPM Universitas Sebelas April, 2025)
This research seeks to examine the impact of independence, accountability, and due professional care on the performance of auditors within the Sumedang Regency Regional Government Inspectorate. This study utilizes a quantitative approach through the implementation of a survey method. The data was collected through the distribution of questionnaires to auditors at the Sumedang Regency Inspectorate and subsequently analyzed using multiple linear regression techniques. The results demonstrate that, both individually and collectively, the three independent variables have a positive and significant impact on auditor performance. The findings highlight the importance of cultivating an independent mindset, improving accountability, and implementing a suitable care approach to attain exceptional audit performance.